P5-S6.14 Qualitative assessment of facilitators and barriers to HPV vaccination among providers serving a high-risk community. (10th July 2011) - Javanbakht, M; Stahlman, S; Walker, S; Gottlieb, S; Markowitz, L; Liddon, N; Plant, A; Guerry, S
Abstract : Background: Maximising HPV vaccine uptake among those at highest risk for cervical cancer is critical. We explored healthcare provider perspectives on factors influencing HPV vaccination among adolescent girls in a community with high cervical cancer rates. Methods: From March to May 2009, we conducted in-depth interviews with 21 physicians and other staff providing care to adolescent girls at two clinics in Los Angeles, CA, serving a predominantly Hispanic population with high cervical cancer rates. The semi-structured interviews explored HPV vaccination processes and potential barriers to vaccination. Results: Providers overwhelmingly focused on parental beliefs as barriers to HPV vaccination, though noted other factors including the lack of school requirements and barriers related to serving a low-income, immigrant clientele. Perceived parental misconceptions acting as barriers included the belief that adolescents do not need vaccinations and that no-cost vaccine programs like Vaccines for Children are only available for younger children. Perceived parental concerns that the vaccine will promote sexual activity were prevalent, especially for parents of 11–12-year-old girls, which prompted providers to frame HPV vaccine as a "routine, " "cervical cancer" vaccine. However, providers felt mothers with experience with abnormal Pap tests and those with a supportive friend or relative were more likely to request HPV vaccine. Providers noted that for Hispanic parents the "preferred" source of information is peers; if the "right people" in the community were supportive of HPV vaccine, parents were more willing to vaccinate. Most providers noted that because HPV vaccine is not "required" for school, it was difficult to get eligible girls into clinic and to reinforce to parents the need for the vaccine. Other barriers included lack of immunisation records among immigrant parents and a difficult-to-reach, mobile clientele. Conclusions: Providers noted a number of barriers to HPV vaccination, including some perceived parental misconceptions that could be addressed with education about the need for adolescent vaccines and available free vaccine programs. Because community support appears particularly important to Hispanic parents, the use of promotoras—peer liaisons between health organisations and the community—may increase HPV vaccine uptake in this population. Future research should explore how well providers' perceptions align with parents' actual concerns.